Pengaruh Suhu Ekstraksi Terhadap Kualitas Natrium Alginat Rumput Laut Sargassum sp. - Pamungkas, Tri Aji; Ridlo, Ali; Sunaryo, Sunaryo (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Sargassum sp. are the living marine resource that are potential as alginate resources. Sodium alginate is used in the food industry, and non food industry, such as for a coagulant, suspending, stabilizers, film formers, gel formation, and emulsifier. The objective of research was to know the effect of temperature exstraction toward quality of alginate, such as rendement, moisture, ashes content, and viscosity of Sargassum sp. Sampling of Sargassum sp. was done in Krakal Beach Gunung Kidul, Yogyakarta. The research method used experimental method and was design completaly Randomized Design (CRD). Samples were extracted by Na2CO3 7 % solution under diffirencees temperature from 40 ºC - 80 ºC, temperature range 10 °C, each treatment 3 times replicated. Correlation between extraction temperature and sodium alginate qualities were showed positive linier model regression for rendement sodium alginate, negative linier regression model for viscosity and moisture, but not significant for ash content. The result showed the highest rendement of sodium alginate was produced on temperature of 80 ºC, that was 28.31% ± 0.48%. The lowest moisture was produced on temperature of 80 ºC, that was 14.97 ± 1.55%. Highest viscosity was produced on temperature 40 ºC, that was 27.25 ± 0.93 cPs.